2009
DOI: 10.1021/jp902194h
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Argon Nanocoating Shift in the OH Stretching Fundamental of n-Propanol: A Combined Experimental and Quantum Chemical Study

Abstract: Supersonic jet Raman spectroscopy reveals an increasing bathochromic shift of the OH stretching vibration in the most stable conformation of propanol with increasing extent of argon nanocoating. It falls short of the bulk matrix limit of 17 cm−1 even at large nozzle distances. Quantum chemical harmonic frequency calculations up to the CCSD(T) level show that this shift cannot be accounted for by individual Ar atoms or even a first solvation layer but instead requires several layers of Ar atoms around the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 82 publications
1
38
0
1
Order By: Relevance
“…34,35 Finally we discuss the nature of the excitation process that is occurring in these mixed 16 The protonated cluster appearance energies agree well with those measured earlier 2 but the photoionization efficiency curve follows the shape of the argon cluster absorption spectrum quite dramatically. This is reflected in the enhancement of signal around 11.5 eV, peaking at 11.92 eV, dropping down and then rising again.…”
supporting
confidence: 81%
“…34,35 Finally we discuss the nature of the excitation process that is occurring in these mixed 16 The protonated cluster appearance energies agree well with those measured earlier 2 but the photoionization efficiency curve follows the shape of the argon cluster absorption spectrum quite dramatically. This is reflected in the enhancement of signal around 11.5 eV, peaking at 11.92 eV, dropping down and then rising again.…”
supporting
confidence: 81%
“…Previous work 61 has shown that this leads to amorphous layers of Ar around the molecules. Figure 3 shows the result in the hydrogen bond fundamental range.…”
Section: A Experimental Spectramentioning
confidence: 90%
“…5 Partial positive charges at the centre and negative charges at the molecule ends 6 lead to a more specific and directional guest-host interaction than for the similarly large argon host. 7 Stepwise nanocoating of hydrogenbonded organic compounds with matrix host molecules in supersonic expansions is a useful tool in understanding gas-to-matrix shifts [8][9][10] and may enable a more rigorous comparison of matrix isolation spectra to theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%